1997
DOI: 10.1136/vr.140.8.199
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of surgical infections in dogs with a single intravenous injection of marbofloxacin: an experimental model

Abstract: Eighteen healthy beagle dogs of both sexes were each given 0, 2 or 4 mg/kg marbofloxacin intravenously before the subcutaneous implantation of a silicon tissue cage. Two millilitres of a suspension containing 1.3 x 10(4) colony forming units (CFU)/ml of Staphylococcus intermedius were then injected into the cage 15 minutes after the intravenous injection. The dogs were clinically assessed immediately, and then two, four, eight and 24 hours after the challenge. Samples of inflammatory fluid were harvested at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
(19 reference statements)
0
8
0
1
Order By: Relevance
“…It does not appear that the differences in elimination half‐life account for the observed differences in the response of skin infections in dogs since enrofloxacin, which has the shortest T ½ ( Table 1), and marbofloxacin, which has the longest T ½ , are both effective when administered once daily 2 –6 . 13 , 14 , 48 , 52 , 53 Likewise, even though there is a range of values for V D among the drugs, this has not translated into a clinical difference. For example, marbofloxacin and orbifloxacin have a V D in the range of 1–2 L g −1 , achieve effective skin concentrations and appear as clinically effective as drugs such as enrofloxacin with a V D of 2.5–5 L kg −1 .…”
Section: Pharmacology and Pharmaceuticsmentioning
confidence: 99%
See 1 more Smart Citation
“…It does not appear that the differences in elimination half‐life account for the observed differences in the response of skin infections in dogs since enrofloxacin, which has the shortest T ½ ( Table 1), and marbofloxacin, which has the longest T ½ , are both effective when administered once daily 2 –6 . 13 , 14 , 48 , 52 , 53 Likewise, even though there is a range of values for V D among the drugs, this has not translated into a clinical difference. For example, marbofloxacin and orbifloxacin have a V D in the range of 1–2 L g −1 , achieve effective skin concentrations and appear as clinically effective as drugs such as enrofloxacin with a V D of 2.5–5 L kg −1 .…”
Section: Pharmacology and Pharmaceuticsmentioning
confidence: 99%
“…Fluoroquinolones also have been used to treat refractory Rickettsial infections, 26 –31 and have been used for the treatment of Bartonella infections in cats 32 . Gruet and others have shown that 2 mg kg −1 of marbofloxacin prevented surgical infections caused by Staphylococcus intermedius (MIC 0.5 μg mL −1 ) 33 . A standard ‘dermal wound model’ utilizing a surgically created skin infection with Escherichia coli and Klebsiella spp.…”
Section: Introductionmentioning
confidence: 99%
“…, 2000; Papich & Riviere, 2009). Other veterinary studies have shown that the ratios necessary for clinical results may not be as high as those reported for laboratory animals and people (Gruet et al. , 1997; Lees & Aliabadi, 2002).…”
Section: Discussionmentioning
confidence: 79%
“…Lower AUC 0fi24 -to-MIC 90 ratios of 35-55 h may be adequate against some infections of Gram-positive bacteria (Wright et al, 2000;Papich & Riviere, 2009). Other veterinary studies have shown that the ratios necessary for clinical results may not be as high as those reported for laboratory animals and people (Gruet et al, 1997;Lees & Aliabadi, 2002).…”
Section: Discussionmentioning
confidence: 79%
“…La marbofloxacina es una fluoroquinolona de segunda generación que exhibe buen margen de seguridad en caninos, excepto por las posibles anormalidades en cartíla-gos en animales jóvenes (9,10). Es una molécula anfótera con mínima ionización en pH fisiológico, particularidad que asociada a su carácter lipofílico y la limitada unión a proteínas plasmáticas en caninos estimada de un 9 % favorece la distribución tisular (1,2,11).…”
Section: Introductionunclassified